Graphic Novels and Comics in Undergraduate and Graduate Medical Students Education: A Scoping Review - Fabrizio Consorti; Sara Fiorucci; Gianfranco Martucci; Silvia Lai (MDPI AG, 2023)
There is an increasing use of graphic novels and comics (GnCs) in medical education, especially-but not only-to provide students with a vicarious learning experience in some areas of clinical medicine (palliative care, difficult communication, and rare diseases). This scoping review aimed to answer questions about how GnCs are used, the theories underlying their use, and the learning outcomes. Twenty-nine articles were selected from bibliographic databases and analyzed. A thematic analysis revealed four many themes: learning outcomes, students' reactions, theories and methods, and use of GnCs as vicarious learning. GnCs can support the achievement of cognitive outcomes, as well as soft skills and professionalism. The reactions were engagement and amusement, but drawing comics was also perceived as a protected space to express concerns. GnCs proved to be a possible way to provide a vicarious experience for learning. We found two classes of theories on the use of GnCs: psychological theories based on the dual concurrent coding of text and images and semiotics theories on the interpretation of signs. All the studies but two were single arm and observational, quantitative, qualitative, or mixed. These results suggest that further high-quality research on the use of GnC in medical training is worthwhile.